EVALUATING CLINICAL ALVARADO SCORING SYSTEM AND CT CRITERIA IN THE DIAGNOSIS OF ACUTE APPENDICITIS - SOHAIL , M; ZAIDI , H; AAMIR , O (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in Combined Military Hospital from January 2021- January 2022 to assess the diagnostic value of CT and the clinical Alvarado scoring system for patients with acute appendicitis. A total of 200 participants were included in the study. Patient details were recorded, including demographic data, radiological findings, Alvarado clinical assessment scoring, and pathological findings. CT evaluation was based on the diameter of the Appendix, presence or absence of appendicolith, peri appendiceal inflammation, and free fluid. Results showed that there was a significant association between CT criteria (free fluid, peri appendiceal inflammation, and appendicolith) and the presence of appendicitis (P=.01). There also was a significant association between Alvarado score and appendicle diameter (P=.01), and also between WBC and appendicle diameter (P=.01). The cut-off value obtained for appendicle diameter was 6.4 mm. Computed tomography is an accurate modality for diagnosing acute appendicitis. CT and Alvarado score systems provide helpful insight for diagnostic workup of suspected cases of acute appendicitis.